INTERNATIONAL REFUGEES AND INDONESIA'S FREE AND ACTIVE FOREIGN POLICY - Jani, Salsabila Andi; Nurislamia, Fika; Deryqa, Khansa (Jurnal Ilmiah Kajian Keimigrasian, 2024)
Indonesia's Free and Active Foreign Policy has influenced the way the country deals with international refugees, especially as a transit country. Although it has not ratified the 1951 Refugee Convention, Indonesia uses domestic legal frameworks, such as Law No. 6/2011 on Immigration, to deal with refugee issues. This research uses a qualitative method with desk-based analysis to examine the relationship between Indonesia's foreign policy and international refugee management. The results show that although Indonesia does not grant asylum, the country provides temporary protection and basic assistance to refugees, in collaboration with international organizations such as UNHCR. The article concludes that Indonesia's Free and Active Foreign Policy plays a role in balancing national interests with humanitarian obligations, demonstrating a commitment to global cooperation despite not yet fully participating in international conventions related to refugees.